(untitled) (Journal of Human Sciences, 2021)
This research deals with an important aspect of the life of the fighter Ahmed Al-Sharif Al-Senussi. Specifically, the research discusses his life after his departure from Libya to the Ottoman Empire in which he lived for six years. It concentrates on his relationship with Mustafa Kemal Ataturk, the founder of the modern state of Turkey and the stages that this relationship went through. This relationship has passed through two stages during this period: The first was characterized by affection and serenity. When Ataturk announced his revolution against the Ottoman Sultan, he was a constant correspondence with Ahmed Sharif, who was residing in the Turkish city of Prussa, and these messages were about reciting Ahmed Sharif’s sympathy and requesting his support for him in his revolution. As for the second stage, it witnessed a fundamental change after the ouster of the Sultan and the abolition of the Islamic Caliphate. This stage ended with Ahmed Sharif’s departure from Turkey